Causes analysis and prevention strategies for falls in elderly patients with diabetes (老年糖尿病患者发生跌倒的原因分析及预防) - GENG Xuejiao (耿雪姣); WANG Huazhi (王华枝); JIA Yinghua (贾英华); LI Meng (李蒙); CAO Yu (曹雨); JIA Shan (贾姗) (中西医结合护理)
Diabetes has become one of major diseases that that seriously threaten human health worldwide. Given the increased risk of falls associated with characteristics of diabetes and its chronic complications, it is required to enhance the falls risk management and increase the awareness of falls prevention in elderly patients with diabetes. This paper briefly analyzed the causes and prevention strategies for falls, in order to provide reference for clinical practice of falls prevention for elderly patients with diabetes. (糖尿病已经成为威胁人类健康的主要疾病之一。由于糖尿病疾病特点和并发症发生会增加跌倒发生的风险, 因此应加强老年糖尿病患者跌倒风险管理, 提高跌倒风险意识。本文简要分析老年糖尿病患者发生跌倒的原因, 总结预防跌倒的措施, 旨在为临床制定和实施老年糖尿病患者跌倒预防干预提供参考。)